Characterization and investigation of the deformation behavior of porous magnesium scaffolds with entangled architectured pore channels. (December 2016) - Jiang, Guofeng; Li, Qiuyan; Wang, Cunlong; Dong, Jie; He, Guo
Abstract: We report a kind of porous magnesium with entangled architectured pore structure for potential applications in biomedical implant. The pore size, spatial structure and Young׳s modulus of the as-prepared porous Mg are suitable for bone tissue engineering applications. Particularly, with regard to the load-bearing conditions, a new analytical model is employed to investigate its structure and mechanical response under compressive stress based on Gibson-Ashby model. It is found that there are three types of stress-strain behaviors in the large range of porosity from 20% to 80%. When the porosity is larger than an upper critical value, the porous magnesium exhibits densifying behavior with buckling deformation mechanism. When the porosity is smaller than a lower critical value, the porous magnesium exhibits shearing behavior with cracking along the maximum shear stress. Between the two critical porosities, both the buckling deformation and shearing behavior coexist. The upper critical porosity is experimentally determined to be 60% for 270 μm pore size and 62% for 400 μm pore size, while the lower critical porosity is 40% for 270 μm pore size and 42% for 400 μm pore size. A new analytical model could be used to accurately predict the mechanical response of the porous magnesium. No matter the calculated critical porosity or yielding stress in a large range of porosity by using the new model are well consistent with the experimental values. All these results could help to provide valuable data for developing the present porous magnesium for potential bio applications. Graphical abstract: Highlights: An entangled porous magnesium for potential biomedical applications was fabricated. Three types of stress-strain behaviors of the porous magnesium were found. Densifying behavior occurs at high porosity, while shearing behavior occurs at low porosity. Two critical porosities were experimentally determined to be 60% and 40%, respectively. A model developed can well simulate the entangled structure and mechanical response.